2010
DOI: 10.1073/pnas.1010560107
|View full text |Cite
|
Sign up to set email alerts
|

Duration of antigen receptor signaling determines T-cell tolerance or activation

Abstract: The early events that determine the decision between lymphocyte tolerance and activation are not well-understood. Using a model of systemic self-antigen recognition by CD4 + T cells, we show, using single-cell biochemical analyses, that tolerance is characterized by transient signaling events downstream of T-cell receptor engagement in the mammalian target of rapamycin (mTOR) and NF-κB pathways. Parallel studies done by live cell imaging show that the key difference between tolerance and activation is the dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 22 publications
4
59
0
Order By: Relevance
“…In untreated sOVA-Tg mice, DO11.10 cells failed to produce high levels of cytokines, as previously reported (7,8,24) (Fig. 2A, 2B).…”
Section: Cd40 Activation Specifically Induces An Il-17 Responsesupporting
confidence: 61%
See 2 more Smart Citations
“…In untreated sOVA-Tg mice, DO11.10 cells failed to produce high levels of cytokines, as previously reported (7,8,24) (Fig. 2A, 2B).…”
Section: Cd40 Activation Specifically Induces An Il-17 Responsesupporting
confidence: 61%
“…Additionally, the generation of Th1 and Th17 effector cells has been shown to be dependent on various other parameters including transcription factors, epigenetic modifications, and CD28 costimulation (2)(3)(4)(5). There is also evidence for temporal differences in the appearance of Th1 and Th17 cells, with most studies showing that the Th17 response peaks early, followed by the appearance of Th1 cells (6)(7)(8)(9). Finally, the development of these subsets is reciprocally regulated, due mainly to the fact that IFN-g is a powerful inhibitor of Th17 differentiation (3,10).…”
Section: Ifferent Subsets Of Effector Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, with the use of isotype antibody staining controls, our observation suggests that cytometric determination may be an invaluable predictor of phosphorylation levels of p56 lck that complements western blot analysis. Indeed our study is in line with previous phosflow protocols ( [41][42][43][44], as already described, mainly, for signaling molecules downstream of TCR-induced stimulation, including Stats, Akt, and S6 (45)(46)(47)(48). Here, in addition to demonstrating that pY416 antibody may be used for cytometric detection of pY394, we have demonstrated that TCR-induced stimulation of human primary T cells led to simultaneous phosphorylation of Y394 and Y505 residues.…”
Section: Discussionsupporting
confidence: 72%
“…Analysis of T cell motility and interactions within the lymph node has established that increased T cell motility and aborted T cell interactions with APCs are associated with tolerance induction, whereas increased duration of T cell arrest and sustained interactions with APCs result in T cell activation 18,19,20,21 . Multiple mechanisms leading to this effect have been demonstrated in the pancreatic lymph nodes of NOD mice.…”
Section: Introductionmentioning
confidence: 99%